STEREOTYPED LANGUAGE ABOUT WOMEN ON INTERNET MEMES OF MEME COMIC INDONESIA (A Multimodal Critical Discourse Analysis) - Ayu Lestari Siregar; Busmin Gurning; Didik Santoso (LINGUISTIK TERAPAN, 2019)
This study examined 21 (twenty one) Internet memes taken from instagram wall of Meme Comic Indonesia (MCI). This studies applied Multimodal Critical Discourse Analysis promoted by Van Leeuwen which particularly in this study was the merger between Three Dimensional of Fairclough and Visual Grammatical of Kress and Van Leeuwen. The results of this study revealed five kinds of stereotyped language about women which are women’s personality traits, women’s cooking domestics behaviour, women’s physical appearances, women’s teaching occupation and women’s driving motorcycle behaviour which considered as new kind of stereotype about women. It is also revealed that the process of realization of stereotyped language about women is by seeing the context of the features used by the creator of the internet memes. The reasons of using stereotyped language about women as humour can be seen as critics and warning attemptions by the creator of the internet memes.Key words: Stereotyped Language about Women, internet memes, Multimodal Critical Discourse Analysis